PHYSIOLOGICAL PERFORMANCE OF ZEA MAYS SEEDS MATRICONDITIONED AT DIFFERENT TEMPERATURES (Colloquium Agrariae. ISSN: 1809-8215, 2020)
The use of high quality seeds reflects directly on crop establishment and productivity. The speed of seed water intake, as well as, temperature during this process is the main factor to have success during germination. The objective of this study was quantifying water uptake from corn seeds during matriconditioning under four temperatures (10, 15, 20 and 25 °C) and seeds without treatment (control) also evaluate physiological quality of those. C1 seed, without chemical treatment, from two different lots of 30F53YH hybrid corn was used. The water content curve was determined from eight replication, of two hundred seeds each, by weighing in intervals of 2; 4; 6; 10; 14; 18; and 24 hours of soaking. In sequence various tests aiming identify physiological seeds quality was developed. With 24-hour evaluation, both group of seeds had higher moisture content when matriconditioned at 25°C. The results allowed concluding that the physiological quality of corn seeds was affected by matriconditioning and the higher imbibition temperatures provided the expression of greater vigor in corn seedlings, being useful for this specie.